Voluntary and involuntary risk acceptance: A case study of firefighters - Rodríguez-Garzón, Ignacio; Martínez-Fiestas, Myriam; Darmohraj, Adrian; Delgado-Padial, Antonio; Chumpitaz, Ruben (Elsevier B.V., 2022)
This article examines how individuals perceive risk depending on whether their exposure to it is voluntarily or not. The study gleans its conclusions by comparing a sample of professional (N = 186) and volunteer (N = 199) firefighters from Buenos Aires (Argentina). The Psychometric Paradigm was selected as the tool to measure risk perception as it yields detailed results from a global perspective based on different attributes and dimensions. The findings reveal significant differences from one group to another. Volunteer firefighters, in fact, reveal lower levels of risk perception that career professionals. Furthermore, a linear hierarchical regression suggests that levels of voluntariness can help predict perception of risk. The study then discusses the different contributions of its findings to academia, to risk management and to the internal marketing of organizations before concluding with a series of recommendations as to potential lines of research.
Keywords: perceived risk; psychometric paradigm; risk perception; volenti non fit iniuria; volenti non fit iniuria, firefighters; voluntariness; Scopus; JCR